96 details: the web is a place to give and share - Paula Varanda (Interfaces)
As the World Wide Web became accessible to society on a global scale during the 1990s, artists that stepped into this technological and aesthetic environment experienced transformative effects to their craft and creativity. For dance, a traditionally ephemeral and corporeal action, the limits and values associated with this condition were susceptible to change. 96 details is the result of dance expert knowledge transferred to new media after persistent research on how to approach the web as a theatre and engage world-wide audiences. With this change of format the choreographers challenged the institutional canons of their field and exceeded spectatorship conventions. Such pioneer experience is a remarkable venture into a new format that extends the understanding of what is dance. As the work becomes technologically obsolete, documenting its efficient making and exchanging process that expands concepts of venue, authorship, embodiment and performance, aims to inspire the future of dance and praise the sharing paradigm of the web.